In order for us to determine the value of (x - y)(x - y), we have to solve for the value of x and y first. To do that, we can use the substitution method. Here are the steps.
1. Rewrite equation 1 xy = 12 in terms of "y" by dividing both sides of the equation by x.
So, equation 1 becomes y = 12/x.
2. Replace the value of y in equation 2 with 12/x.
Then, solve for x.
Add the terms on the left side of the equation. Use x² as the GCD.
Cross multiply.
Then, we factor the quartic polynomial. In order to factor, just answer the question "what are the factors of 144 that add to -25?".
The factors are -16 and -9. Hence, we can rewrite the equation as:
Then, divide the equation into two groups.
Then, factor out x² in the first group and factor out 16 in the second group.
Since x² - 9 is a common factor on both groups, we can just rewrite it as:
Then, equate each factor to zero. Then, solve for x.
Therefore, there are 4 possible values of x. These are +4, -4, +3, and -3.
Since xy = 12, then:
1. At x = 4, y = 3.
2. At x = -4, y = -3.
3. At x = 3, y = 4.
4. At x = -3, y = -4.
Let's plug the pairs of x and y in the expression (x - y)(x - y) and solve.
On all pairs, the value of (x - y)(x- y) is 1. Hence, the answer is 1.